Influencer Marketing as a Tool of Digital Consumer Engagement : A Systematic Literature Review - Tanwar, Anshika Singh; Chaudhry, Harish; Srivastava, Manish Kumar (Indian Journal of Marketing, 2021)
Influencer marketing is a recently emerging strategy that involves engaging people who are influential in the digital domain to share sponsored content of a brand with their followers. The purpose of this article was to review the published literature on influencer marketing, conduct a content analysis of the academic literature, and furnish a classification based on different parameters. The content analysis led to a distribution of articles as per eight different categories. This article provided the first such literature review of influencer marketing literature for the period from 2008 – 2019 to analyze and present the trends of this new marketing tactic, industries and fields involved, different platforms of social media used, key areas and methods employed by the social media influencers to connect with their followers, and spread a brand message. It was found that the major focus areas and industries utilizing social media influencers (SMIs) for brand messages and engagement of the digital consumers are lifestyles, fashion, and beauty. Empirical research was found to be predominant during the period under study. The most popular issues in the recent studies were self-presentation, para-social interactions, para-social relationships, and the credibility of the SMIs.